2014
DOI: 10.4236/ojog.2014.411090
|View full text |Cite
|
Sign up to set email alerts
|

Pica Practices among Pregnant Women Are Associated with Lower Hemoglobin Levels and Pregnancy Outcome

Abstract: Pica is an eating disorder in which non-nutritional objects are frequently eaten, and may have serious side effects for both the mother and neonate. The aim of this study was to determine the pica and its association with biochemical profiles of pregnant women and its relation to pregnancy outcome. A prospective cohort study was conducted in five health care centers in Zahedan City, Iran, in 2011-2012. Samples of pregnant women (n = 200) in the age groups 18-40 years were selected for this study and interviewe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
16
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 11 publications
4
16
2
Order By: Relevance
“…When a logistic regression was performed, they were 1.23 times more likely to be anaemic. The relationship between pica and anaemia has been documented in other studies [5, 21]. Therefore, in spite of the low prevalence reported in this study, it is still prudent to educate pregnant women and adolescents against practicing pica because of its reported link to anaemia in pregnancy and incidence of lead poisoning [22].…”
Section: Discussionmentioning
confidence: 59%
“…When a logistic regression was performed, they were 1.23 times more likely to be anaemic. The relationship between pica and anaemia has been documented in other studies [5, 21]. Therefore, in spite of the low prevalence reported in this study, it is still prudent to educate pregnant women and adolescents against practicing pica because of its reported link to anaemia in pregnancy and incidence of lead poisoning [22].…”
Section: Discussionmentioning
confidence: 59%
“…These complications vary depending on the type of pica (Ekwenchi, Duru, Ononiwu, & Ezeigbo, ). In a study conducted by Khoushabi et al (), findings indicated the association between pica and low maternal haemoglobin levels during childbirth and iron deficiency.…”
Section: Discussionmentioning
confidence: 96%
“…Maternal under nutrition results in increased risks of short‐term consequences such as intrauterine growth restriction (IUGR), low birth weight, preterm birth, prenatal and infant mortality and morbidity (Fekadu Beyene, ). In a study conducted by Khoushabi et al () reported that mothers could suffer from dental injuries, intestinal obstructions, toxaemia, constipation, lead poisoning, parasitic infections and hyperkalaemia if the intake of pica becomes pervasive. Myths and misunderstanding surrounding eating of non‐food items can expose pregnant women to serious health consequences.…”
Section: Introductionmentioning
confidence: 99%
“…Medical records, observed no differences in mean birth weight of infants born to women from pica practiced group and the non pica group. However, Khousabi et al [40] found that pica has adverse effects on pregnancy outcomes in Iran. Kariuki et al [41] among the Western Kenyan pregnant women, observed pica prevalence at 27.4%, with consumption of soil and soft stones being frequently reported.…”
Section: Discussionmentioning
confidence: 99%